2019
DOI: 10.4274/balkanmedj.galenos.2018.2018.0704
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cerebral Blood Flow Alterations and Acute Neuronal Damage due to Water-Pipe Smoking

Abstract: Background:Although water-pipe smoking is a great public health problem, data regarding the acute and chronic effects and the degree of toxin exposure are limited. While water pipe-related malignancy, pulmonary, infectious, cardiac effects, infertility, and biological effects have been described in a meta-analysis, there are no studies in the literature about its neurologic effects.Aims:To evaluate water pipe-related acute neurological effects and cerebral blood flow through transcranial Doppler ultrasonograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A clinical study has reported a reduced level of circulating brain-derived neutrophic factor in adolescent WPS smokers [ 25 ]. A prospective observational study has reported that exposure to WPS causes neuronal damage through the increase in cerebral blood flow rate, elevation in carboxyhemoglobin and S100 calcium-binding protein [ 26 ]. Furthermore, adverse effects on cognitive executive measures were recorded in humans following one session of WPS inhalation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…A clinical study has reported a reduced level of circulating brain-derived neutrophic factor in adolescent WPS smokers [ 25 ]. A prospective observational study has reported that exposure to WPS causes neuronal damage through the increase in cerebral blood flow rate, elevation in carboxyhemoglobin and S100 calcium-binding protein [ 26 ]. Furthermore, adverse effects on cognitive executive measures were recorded in humans following one session of WPS inhalation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%